Preferred pedalling cadence in professional cycling - Lucia, A.; Hoyos, J.; Chicharro, J. L. (Medicine & Science in Sports & Exercise, 2001)
Purpose: The aim of this investigation was to evaluate the preferred cycling cadence of professional riders during competition. Methods: We measured the cadence of seven professional cyclists (28 +/- 1 yr) during 3-wk road races (Giro d'Italia, Tour de France, and Vuelta a Espana) involving three main competition requirements: uphill cycling (high mountain passes of approximately 15 km, or HM); individual time trials of approximately 50 km on level ground (TT); and flat, long ( approximately 190 km) group stages (F). Heart rate (HR) data were also recorded as an indicator of exercise intensity during HM, TT, and F. Results: Mean cadence was significantly lower (P < 0.01) during HM (71.0 +/- 1.4 rpm) than either F and TT (89.3 +/- 1.0 and 92.4 +/- 1.3 rpm, respectively). HR was similar during HM and TT (157 +/- 4 and 158 +/- 3 bpm) and in both cases higher (P < 0.01) than during F (124 +/- 2 bpm). Conclusion: During both F and TT, professional riders spontaneously adopt higher cadences (around 90 rpm) than those previously reported in the majority of laboratory studies as being the most economical. In contrast, during HM they seem to adopt a more economical pedalling rate ( approximately 70 rpm), possibly as a result of the specific demands of this competition phase.